Association of tax haven and corporate tax avoidance: does political connection matter? - Kurniasih, Lulus; Yusri, Yusniyati; Syekh Hassan, Ahmad Fahmi (Universiti Putra Malaysia, 2022)
This study specifically examines the association between tax haven and corporate tax avoidance, along with the role of political connection in the association. We use two types of corporate tax avoidance measurements to capture corporate tax avoidance as a whole and the specific profit-shifting scheme. Based on the data of Indonesian multinational companies (MNC) over the 2010–2019 period, we find that MNC with tax haven affiliation is positively associated with corporate tax avoidance. Moreover, our result indicates that political connection significantly moderates the association of tax haven affiliation and corporate tax avoidance.